2021
DOI: 10.1109/access.2021.3121750
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning and Geospatial Data-Based Channel Estimation Technique for Hybrid Massive MIMO Systems

Abstract: This paper presents a novel channel estimation technique for the multi-user massive multiple-input multiple-output (MU-mMIMO) systems using angular-based hybrid precoding (AB-HP). The proposed channel estimation technique generates group-wise channel state information (CSI) of user terminal (UT) zones in the service area by deep neural networks (DNN) and fuzzy c-Means (FCM) clustering. The slow time-varying CSI between the base station (BS) and feasible UT locations in the service area is calculated from the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 34 publications
(47 reference statements)
0
23
0
Order By: Relevance
“…is the trace operation. It is worth mentioning that, channel characteristics at the transmitter can be obtained via both online and offline approaches (Zheng et al, 2018;Wang et al, 2015;Zhu et al, 2021). The received signal vector after analog combiner can be stated as follows:…”
Section: Hybrid Beamforming Architecturementioning
confidence: 99%
“…is the trace operation. It is worth mentioning that, channel characteristics at the transmitter can be obtained via both online and offline approaches (Zheng et al, 2018;Wang et al, 2015;Zhu et al, 2021). The received signal vector after analog combiner can be stated as follows:…”
Section: Hybrid Beamforming Architecturementioning
confidence: 99%
“…are the weight matrix and bias vector, respectively. In order to fit the output layer predictions between 0 and 1 as in the output labels expressed in (14), we employ the sigmoid function at the output layer (i.e., f σ (x) = 1 1+e −x [11]). Thus, the predicted power values for K downlink UEs via the DNN architecture are written as:…”
Section: A Deep Neural Network Architecturementioning
confidence: 99%
“…As a key driving force for artificial intelligence (AI), deep learning has been successfully applied in many fields including computer vision, speech recognition and natural language processing [11]. Hence, the success of deep learning also motivates its applications in wireless communication systems [12]- [14]. For instance, deep learning has been applied for signal detection [12], resource management [13], channel estimation [14].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the URA structure, Mx and My denote the number of antennas along x-axis and y-axis, respectively. There are two main reasons for utilizing the URA structure: (i) it packs a larger number of antennas in a twodimensional (2D) grid under the physical-limited space requirements in practical applications, (ii) it enables three-dimensional (3D) beamforming by employing both azimuth and elevation domains[2],[5]-[7],[12],[16] 3. Since the analog RF beamformer is designed via the AoD information, it is reasonable to assume that each subcarrier experiences a similar AoD support (i.e., mean azimuth/elevation AoD and their spread).…”
mentioning
confidence: 99%
“…In[16], it is shown that the AoD parameters (i.e., mean and spread) can be efficiently obtained via an offline deep learning and geospatial data-based estimation technique instead of the traditional online channel sounding.…”
mentioning
confidence: 99%